Sport, Statehood and Transition in Europe. Comparative perspectives from post-Soviet and post-socialist societies (Routledge, 2020)
This book examines the political significance of sport and its importance for nation-state building and political and economic transition across thirteen post-Soviet and post-socialist countries, primarily located in Eastern Europe.